Surface Treatments for Repair of Feldspathic, Leucite - and Lithium Disilicate-Reinforced Glass Ceramics Using Composite Resin - Neis,Christian Alencar (2015)
The aim of this study was to evaluate the efficacy of different surface conditioning methods on the microtensile bond strength of a restorative composite repair in three types of dental ceramics: lithium disilicate-reinforced, leucite-reinforced and feldspathic. Twelve blocks were sintered for each type of ceramic (n=3) and stored for 3 months in distilled water at 37 °C. The bonding surface of ceramics was abraded with 600-grit SiC paper. Surface treatments for each ceramic were: GC (control) - none; GDB - diamond bur #30 µm; GHF - hydrofluoric acid (10%); GT- tribochemical silica coating (45-μm size particles). Treatments were followed by cleaning with phosphoric acid 37% for 20 s + silane + adhesive. The composite resin was used as restorative material. After repair, samples were subjected to thermocycled ageing (10,000 cycles between 5 °C and 55 °C for 30 s). Thereafter, the samples were sectioned into 1.0 mm2 sticks and tested for microtensile bond strength with 0.5 mm/min crosshead speed. Data were compared by two-way ANOVA and Tukey's test (α=0.05). The superficial wear with diamond bur proved to be suitable for feldspathic porcelain and for leucite-reinforced glass ceramic while hydrofluoric acid-etching is indicated for repairs in lithium disilicate-reinforced ceramic; tribochemical silica coating is applicable to leucite-reinforced ceramic. Predominance of adhesive failures was observed (>85% in all groups). In conclusion, the success of surface treatments depends on the type of ceramic to be repaired.